Carotid intima-media thickness and risk of atherosclerosis in multiple sclerosis: A cross-sectional study. - Elyar Alizadeh Najmi; Zahra Mirzaasgari; Mohammad Reza Motamed; Armin Aslani (PLoS ONE)
Background Multiple sclerosis (MS) is characterized by inflammation and demyelination in the central nervous system. Recent studies have suggested a potential association between MS and an increased risk of atherosclerosis, a systemic vascular disease involving arterial wall thickening. Understanding this relationship is crucial, given the heightened cardiovascular risk observed in MS patients. Objective To investigate factors influencing the development of atherosclerosis in patients with multiple sclerosis (pwMS), focusing on carotid intima-media thickness (CIMT) as a marker. Methods 114 pwMS (82 females and 32 males) and 127 control subjects (57 females and 70 males) were included. The mean CIMT between the two groups was compared. Additionally, the effects of annual relapse rate, EDSS (Expanded Disability Status Scale), MS duration, treatment duration, and type of Disease-modifying treatment (DMT) on CIMT were evaluated. Results This study included 241 participants with a mean (SD) age of 41.13 years (10.93). CIMT was significantly higher in pwMS compared to controls (p < 0.001). Even after adjusting for age, sex, and BMI (Body Mass Index), CIMT remained significantly higher in the pwMS group (p < 0.001). Spearman's correlation analysis revealed significant associations between CIMT and age, BMI, EDSS score, and disease duration (all p < 0.05). Additionally, the SPMS (Secondary Progressive Multiple Sclerosis) disease course was significantly associated with higher CIMT (p < 0.001). Linear regression analysis identified age as the most significant predictor of increased CIMT in pwMS (p < 0.001), followed by BMI (p = 0.054). Conclusion This study demonstrates a significant association between MS and increased CIMT. Additionally, age emerged as the most prominent predictor of high CIMT in pwMS, followed by BMI. These findings suggest a potential link between MS and increased cardiovascular risk. Further research is warranted to explore the underlying mechanisms and investigate the long-term cardiovascular outcomes in this population.